2018
DOI: 10.17219/acem/78775
|View full text |Cite
|
Sign up to set email alerts
|

Withholding and withdrawing life-sustaining treatment: Experiences in limiting futile therapy from three Polish intensive care departments

Abstract: Background. In intensive care units (ICUs), a patient's vital functions may be maintained, regardless of the patient's chances of survival. A key issue is how to precisely determine the moment in which life-support treatment should be withheld. In many countries, the decision-making process is regulated by the guidelines of scientific societies. However, heuristic errors may influence this process. Objectives. The objective of this study was to assess factors involved in decisions to implement or withhold trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…In a study about withholding and withdrawal practices for life-sustaining treatments, no association was found between withholding treatment and age. However, the authors of the study found a correlation between withholding treatment and the duration of ICU stay [20].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study about withholding and withdrawal practices for life-sustaining treatments, no association was found between withholding treatment and age. However, the authors of the study found a correlation between withholding treatment and the duration of ICU stay [20].…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the need to promote protocols for screening and the effective implementation of ELM-PC in ICU teams is still a necessity, at least in the population and in the region addressed in this study. A significant relationship has been found between the application of a "do not resuscitate" (DNR) order and withholding noradrenaline treatment in the hours preceding the patient's death [20].…”
Section: Discussionmentioning
confidence: 99%
“…Religion, years in practice or institution did not affect their agreement, but religiosity, physician specialty and responsibility for end-of-life decisions did [ 17 ]. Only one recently published study in an intensive care unit described a relation between a DNAR order in a patient’s documentation and the frequency of both resuscitation procedures and withholding catecholamine treatment in the hours preceding a patient’s death [ 18 ]. The complexities of the decision not to perform CPR in pediatric hospital settings were recently described as discrepancies identified between practice and medical records in DNR pediatric patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à idade, estudo francês (Nesseler et al, 2018) converge com os achados desta revisão, indicando relação entre idade avançada e limitação de tratamentos mantenedores da vida. Já estudo realizado em UTI's na Polônia encontrou resultados divergentes, não evidenciando relação significativa entre idade e a suspensão de uso de vasopressores (Siewiera et al, 2019). Igualmente, constatou que médicos possuem maior propensão em limitar tratamentos como coleta de gasometria, prescrição de vasopressores ou correção sérica de sódio e potássio, do que retirá-los por completo.…”
Section: Discussionunclassified